Stereoselective synthesis of (1R, 2S)-norephedrine by recombinant whole-cell biocatalysts coupling acetohydroxyacid synthase I and ω-transaminase. (October 2018) - Lee, Yen-Chung; Chen, Yih-Yuan; Lin, Jian-Sin; Chen, Yi-Wun; Li, Chia-Chen; Liang, Kun-Xin; Chan, Hsin-Hua; Lin, Wei-De; Kao, Chao-Hung
Graphical abstract: Highlights: Whole-cell biocatalysts were constructed for (1 R, 2 S )-norephedrine (NE) production. The conversion yield of L-phenylacetylcarbinol was almost 100% in a 2-h reaction. The conversion yield of (1 R, 2 S )-NE was 62.2% with 99% of enantiomeric excess. The recombinant whole cell biocatalyst can be reused for at least 20 cycles. Abstract: In this study, a combined whole-cell biotransformation process was used for efficient synthesis of optically pure (1 R, 2 S )-norephedrine [(1 R, 2 S )-NE]. The genes encoding R -selective acetohydroxyacid synthase I (AHAS I) from Escherichia coli and S -selective ω-transaminase (ω-TA) from Chromobacterium violaceum BCRC10636 were cloned and over-expressed in E. coli NovaBlue cells. In the first biosynthetic step, l -phenylacetylcarbinol (l -PAC) was produced from benzaldehyde and pyruvate by using recombinant E. coli (pQE- AHAS I) cells, with almost 100% conversion yield and 71.8% purification yield. The purifiedl -PAC was coupled tol -alanine by using recombinant E. coli (pQE- CvTA ) cells to produce (1 R, 2 S )-NE. This biocatalytic process was optimal at pH 6.5 to 8.0 and 37 °C, with a 1:10 ratio ofl -PAC tol -alanine. Under the optimal conditions, the highest conversion yield of (1 R, 2 S )-NE was 62.2% and the enantiomeric excess value of (1 R, 2 S )-NE was more than 99%. The recombinant E. coli (pQE- CvTA ) cells could be reused for at least 20 cycles, with only a modest reduction in the conversion yield to 76.3% relative to the first cycle. Our results indicate that the combination of AHAS I- and ω-TA-expressing E. coli cells might be a potential biocatalyst for (1 R, 2 S )-NE production.